THE IMPACT OF LEADERSHIP COMPETENCY AND SUPPORTIVE WORK ENVIRONMENT ON EMPLOYEE WORK MOTIVATION OF PT SINAR SOSRO MARKETING DIVISION SURABAYA - Indriyani, Ratih; Suprapto, Widjojo; Tjok, Daniel Kusuma (Penerbit Atma Jaya Catholic University of Indonesia, 2019)
This study aims to investigate the impact of leadership competencies and supportive work environment on work motivation of marketing division employees at PT Sinar Sosro in Surabaya. The data is collected using the questionnaires that are distributed among the employees of the marketing division. There are 90 valid returned questionnaires from the respondents, who are selected using the census method. The results of the study show that leadership competencies have a significant and positive influence on the employees? work motivation. The supportive work environment has a significant and positive influence on the employees? work motivation. The leadership competency and the supportive work environment have a significant and positive effect on work motivation simultaneously